2022
DOI: 10.1098/rstb.2021.0319
|View full text |Cite
|
Sign up to set email alerts
|

Inositol 1,4,5-trisphosphate receptors in cardiomyocyte physiology and disease

Abstract: The contraction of cardiac muscle underlying the pumping action of the heart is mediated by the process of excitation-contraction coupling (ECC). While triggered by Ca 2+ entry across the sarcolemma during the action potential, it is the release of Ca 2+ from the sarcoplasmic reticulum (SR) intracellular Ca 2+ store via ryanodine receptors (RyRs) that plays the major role in induction of contraction. Ca 2+ also acts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 153 publications
0
7
0
Order By: Relevance
“…GPCR agonists that we and others have previously used to stimulate InsP 3 production in CM also engage multiple kinase cascades, which in turn influence the activity of NCX, L-type current, myofilaments and NHE with consequences for Ca 2+ dynamics and contractility [25,31,34,58,59]. Since we aimed in this study to specifically probe the influence of InsP 3 R activation on CM physiology, we chose to directly activate InsP 3 Rs with InsP 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GPCR agonists that we and others have previously used to stimulate InsP 3 production in CM also engage multiple kinase cascades, which in turn influence the activity of NCX, L-type current, myofilaments and NHE with consequences for Ca 2+ dynamics and contractility [25,31,34,58,59]. Since we aimed in this study to specifically probe the influence of InsP 3 R activation on CM physiology, we chose to directly activate InsP 3 Rs with InsP 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Ventricular CMs also express inositol 1,4,5'-trisphosphate receptor (InsP 3 Rs) Ca 2+ release channels (the type 2 isoform, InsP 3 R2) [21][22][23][24][25]; their expression and conductance are however substantially lower than RyRs [26][27][28]. While induction of inotropy and arrhythmogenic activity have been reported, effects of InsP 3 -induced Ca 2+ release (IICR) in healthy CM, are if detected, generally modest and vary between studies and species [23,25,29,30].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, levels of IP 3 signaling and expression of IP 3 R were shown to increase in various cardiac pathologies such as cardiac hypertrophy [11], HF [3,11] or AF [13]. While IP 3 dependent regulation of gene transcription contributing to hypertrophic remodeling of atria and ventricles was clearly demonstrated [11,13,53], the role of enhanced IP 3 signaling in pathophysiological atrial ECC and arrhythmogenesis is less clear. Our previous study has demonstrated that in our HF model IP 3 signaling in atria is increased leading to enhanced atrial contractility [3].…”
Section: Modulation Of Ip 3 Signaling Pathways Affects Development Of...mentioning
confidence: 99%